The Historical Aspects and Tendencies of Auditing System Development - Pečiūrienė, Aleksandra (Ekonomika, 2001)
Successful development of the modern auditing system in the Lithuanian market economy is impossible without its history’s analysis and evaluation of the main development tendencies. Widespread auditing klasification by volume and performers and “wide” auditing concept treatment is accepted. Main directions and features of the auditing evolution since antiquity are determined. Six stages of auditing development are proposed. Prospects for the Lithuanian auditing in the modern regional harmonization and worldwide internacionalization, as well as innovations processes of the auditing activities, are observed in the paper.